Flame-retardant PVC-ABS alloy material with high impact resistance and preparation method thereof

A two-step treated titanium dioxide and specially treated chlorinated paraffin enhance the PVC-ABS alloy's tensile strength, impact resistance, and processing performance, addressing the material's deficiencies in existing formulations.

CN119144098AInactive Publication Date: 2024-12-17SHANDONG YUANBANG NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411608616.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing PVC-ABS alloy materials face issues with impact resistance, tensile strength, bending performance, and processing performance due to the addition of inorganic fillers, which compromise the material's overall properties.

Method used

A two-step treatment process is applied to titanium dioxide to create glycidyl ester-modified titanium dioxide, and chlorinated paraffin is specially treated, combined with specific ratios of PVC resin, ABS resin, and other components to form a flame-retardant PVC-ABS alloy material.

Benefits of technology

The resulting alloy material exhibits enhanced tensile strength, impact resistance, bending performance, and improved processing characteristics while maintaining high flame retardancy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a flame-retardant PVC-ABS (polyvinyl chloride-acrylonitrile-butadiene-styrene) alloy material with high impact resistance and a preparation method of the flame-retardant PVC-ABS alloy material, and belongs to the field of high-molecular compound compositions. The alloy material comprises the following raw materials: PVC resin, ABS resin, chlorinated polyethylene resin, glycidyl ester modified titanium dioxide, modified chlorinated paraffin, a plasticizer, a lubricant and a flame retardant. The alloy material disclosed by the invention is good in processability and small in processing torque, the balance torque and the maximum torque of the alloy material are measured by using a torque rheometer, the balance torque is 36.8-37.7 Nm, and the maximum torque is 44.2-45.1 Nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-impact flame-retardant PVC-ABS alloy material and a preparation method thereof, belonging to the field of polymer compound compositions. Background Art

[0002] In recent years, countries around the world have increasingly stringent requirements for the flame retardancy of household appliances, while ABS, which is widely used in such products, is not flame retardant itself. ABS resin contains side phenyl groups, nitrile groups and unsaturated double bonds, and it has good compatibility with many polymers, which creates conditions for the blending modification of ABS.

[0003] PVC-ABS alloy material is a new type of polymer alloy material made by blending and modifying general-purpose plastic PVC and engineering plastic ABS. ABS is blended and modified with PVC with flame retardant properties. The prepared PVC-ABS alloy has excellent flame retardant and mechanical properties at the same time. It can replace ABS in household appliances, plug boards and other products. At the same time, ABS toughening PVC is still one of the important methods to change the processing properties and brittleness of PVC.

[0004] The impact resistance of PVC material itself is poor, while the chlorine atoms in PVC and the nitrile groups in ABS are strong polar groups, so the blending of ABS and PVC can improve its interfacial adhesion, and at the same time make the rubber phase particles in ABS dispersed as the dispersed phase in the continuous phase PVC to form an "island structure". When the material is impacted by external force, silver streaks will be induced at the interface of the two phases to absorb the impact energy, and the mutual interference between the silver streaks will lead to the termination of the silver streaks. As the proportion of ABS in the blend increases, it is conducive to the initiation of silver streaks and the generation of a large number of shear bands with the resin phase, which can absorb higher impact energy and make the material have stronger impact toughness.

[0005] Therefore, in PVC-ABS alloy materials, with the increase of ABS, the impact strength of the material will gradually increase. The impact strength of the material reaches its peak when the ABS content is 50-70%, but after reaching the critical point, the impact strength of the material will decrease. This is due to the decrease in the compatibility of the alloy. It will not reach its peak again until the ABS content is 100%. In addition, the higher the ABS content in the PVC-ABS alloy material, the lower the tensile strength of the material. Therefore, for the comprehensive consideration of material properties, it is particularly important to choose a suitable raw material ratio. It is acceptable to sacrifice part of the tensile properties. In order to make up for the lack of tensile properties, some inorganic substances can be appropriately added to reinforce the material. However, with the addition of inorganic fillers, the processing performance of the material will decrease, which is specifically manifested as an increase in processing torque. In addition, the final bending performance of the material will deteriorate and the bending strength will decrease. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the defects of the prior art, subject titanium dioxide to two-step special treatment, use glycidyl ester-modified titanium dioxide as an inorganic filler, and subject chlorinated paraffin to special treatment, and finally prepare an alloy material, while lowering the material processing performance and processing torque, improving the material's bending performance and ensuring the material's tensile strength.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions: A flame-retardant PVC-ABS alloy material with high impact resistance. The raw materials of the alloy material include PVC resin, ABS resin, chlorinated polyethylene resin, glycidyl ester-modified titanium dioxide, modified chlorinated paraffin, plasticizer, lubricant and flame retardant. The mass ratio of the raw material components is 43-47:6.5-7.5:52-58:1.8-2.2:0.9-1.1:0.45-0.55:0.75-0.85:0.45-0.55.

[0008] The following are further improvements to the above technical solution: The model of the PVC resin is S-550; The model of the ABS resin is DA-05-B; The model of the chlorinated polyethylene resin is CPE-132-C; The plasticizer is dioctyl terephthalate; The lubricant is tetrapentyl stearate; The flame retardant is antimony trioxide; The preparation method of the glycidyl ester-modified titanium dioxide comprises acetoacetic acid treatment and glycidyl ester modification; The method of the acetoacetic acid treatment is: The temperature is controlled to be 1350-1450° C., titanium dioxide is placed in a muffle furnace for calcination, the calcination time is 350-370 minutes, and after the calcination is completed, it is naturally cooled to room temperature, and then mixed with acetoacetic acid solution, the temperature is controlled to be 4-6° C., the stirring speed is controlled to be 1250-1750 r / min, and rapid stirring is performed for 4-6 minutes. After the stirring is completed, it is washed and dried to obtain acetoacetic acid treated titanium dioxide; The mass ratio of the titanium dioxide to the acetoacetic acid solution is 6.5-7.5:40; The titanium dioxide is rutile titanium dioxide with a particle size of 17 μm; The concentration of the acetoacetic acid solution is 7.0-8.0 wt %.

[0009] The glycidyl ester modified method is: The titanium dioxide treated with acetoacetic acid is mixed with tetrahydrofuran, and stirred evenly to obtain a titanium dioxide dispersion, and then glycidyl acrylate is added to the titanium dioxide dispersion, and the temperature is controlled to be 18-22° C. and stirred for 75-85 minutes. After the stirring is completed, the temperature is adjusted to 52-58° C. and the stirring is continued for 14.5-15.5 hours. After the stirring is completed, the titanium dioxide modified with glycidyl acrylate is obtained by filtering, washing with alcohol, and drying; The mass ratio of the acetoacetic acid treated titanium dioxide, tetrahydrofuran and glycidyl acrylate is 6.5-7.5:35-45:10-14.

[0010] The preparation method of the modified chlorinated paraffin is: The chlorinated paraffin and ether are mixed and stirred to completely dissolve to obtain a chlorinated paraffin ether solution, and then the stirring speed is controlled to be 50-70 r / min, and 2-thiol methylbenzimidazole and polyglycerol-10 polyricinoleate are added to the chlorinated paraffin ether solution while the stirring is kept constant. After the addition is completed, the temperature is controlled to be 65-69° C., the stirring speed is controlled to be 100-150 r / min, and the stirring is performed for 50-70 minutes. After the stirring is completed, the solvent ether is evaporated to obtain a modified chlorinated paraffin; The mass ratio of the chlorinated paraffin to ether is 10:60-70; The mass ratio of the ether solution of the chlorinated paraffin, 2-thiol methylbenzimidazole, and polyglycerol-10 polyricinoleate is 750-1250:4.5-5.5:27-38; The model of the chlorinated paraffin is chlorinated paraffin 70#.

[0011] The preparation method of the PVC-ABS alloy material is: PVC resin, chlorinated polyethylene resin, modified chlorinated paraffin, plasticizer and lubricant of specified mass in the raw materials are mixed in a high-speed mixer at a temperature of 115-125°C for 15-25 minutes. After the mixing is completed, ABS resin and glycidyl ester-modified titanium dioxide of specified mass in the raw materials are added into the mixer, the temperature is adjusted to 185-195°C, and the mixing is carried out for 25-35 minutes. After the mixing is completed, extrusion granulation is carried out to obtain PVC-ABS alloy material.

[0012] Compared with the prior art, the present invention achieves the following beneficial effects: The alloy material of the present invention has excellent tensile properties. The sample is prepared according to the method in GB / T1040.1-2018, and the tensile strength and tensile modulus of the alloy material are tested. The tensile strength is 47.6-48.4 MPa, and the tensile modulus is 971-985 MPa. The alloy material of the present invention has excellent impact resistance. The sample is prepared according to the method in GB / T1043.1-2008, and the impact strength of the alloy material is tested. The notched impact strength is 51.4-52.3 KJ / m 2 , unnotched impact strength is 147.2-152.0KJ / m 2 ; The alloy material of the present invention has excellent bending performance. The sample is prepared according to the method in GB / T9341-2008, and the bending strength and bending modulus of the alloy material are tested. The bending strength is 64.7-66.1MPa, and the bending modulus is 2084-2114MPa. The alloy material of the present invention has a high flame retardancy. According to the method in ANSI / UL94-2018, the flame retardancy of the alloy material is tested, and the flame retardancy is V0. The alloy material of the present invention has good processing performance and small processing torque. The equilibrium torque and maximum torque of the alloy material are measured by using a torque rheometer. The equilibrium torque is 36.8-37.7 Nm, and the maximum torque is 44.2-45.1 Nm. The alloy material of the invention has good thermal stability. A sample is prepared according to the method in GB / T1633-2000, and the Vicat softening temperature of the alloy material is detected, and the Vicat softening temperature is 93.2-93.8°C. A sample is prepared according to the method in GB / T2917.1-2002, and the static thermal stability of the alloy material is detected, and the Congo red discoloration time is 64-71min. A thermogravimetric analyzer is used to measure the initial decomposition temperature, and the initial decomposition temperature of the alloy material is 264.5-266.2°C. DETAILED DESCRIPTION Example 1

[0013] A highly impact-resistant flame-retardant PVC-ABS alloy material, wherein the raw materials include PVC resin, ABS resin, chlorinated polyethylene resin, glycidyl ester-modified titanium dioxide, modified chlorinated paraffin, plasticizer, lubricant, and flame retardant, and the mass ratio of the raw material components is 45:7:55:2:1:0.5:0.8:0.5; The model of the PVC resin is S-550; The model of the ABS resin is DA-05-B; The model of the chlorinated polyethylene resin is CPE-132-C; The plasticizer is dioctyl terephthalate; The lubricant is tetrapentyl stearate; The flame retardant is antimony trioxide; The preparation method of the glycidyl ester-modified titanium dioxide comprises acetoacetic acid treatment and glycidyl ester modification; The method of the acetoacetic acid treatment is: The temperature is controlled at 1400° C., titanium dioxide is placed in a muffle furnace for calcination, the calcination time is 360 minutes, and after the calcination is completed, it is naturally cooled to room temperature, and then mixed with acetoacetic acid solution, the temperature is controlled at 5° C., the stirring speed is controlled at 1500 r / min, and rapid stirring is performed for 5 minutes. After the stirring is completed, it is washed and dried to obtain acetoacetic acid treated titanium dioxide; The mass ratio of the titanium dioxide to the acetoacetic acid solution is 7:40; The titanium dioxide is rutile titanium dioxide with a particle size of 17 μm; The concentration of the acetoacetic acid solution is 7.5 wt %.

[0014] The glycidyl ester modified method is: The titanium dioxide treated with acetoacetic acid is mixed with tetrahydrofuran and stirred evenly to obtain a titanium dioxide dispersion, and then glycidyl acrylate is added to the titanium dioxide dispersion, the temperature is controlled to be 20°C, and the stirring is performed for 80 minutes. After the stirring is completed, the temperature is adjusted to 55°C, and the stirring is continued for 15 hours. After the stirring is completed, the titanium dioxide modified with glycidyl acrylate is obtained by filtering, washing with alcohol, and drying. The mass ratio of the acetoacetic acid treated titanium dioxide, tetrahydrofuran and glycidyl acrylate is 7:40:12.

[0015] The preparation method of the modified chlorinated paraffin is: The chlorinated paraffin and ether are mixed and stirred to completely dissolve to obtain an ether solution of the chlorinated paraffin, and then the stirring speed is controlled to 60 r / min, and 2-thiol methylbenzimidazole and polyglycerol-10 polyricinoleate are added to the ether solution of the chlorinated paraffin while maintaining continuous stirring. After the addition is completed, the temperature is controlled to 67° C., the stirring speed is controlled to 120 r / min, and stirring is performed for 60 minutes. After the stirring is completed, the solvent ether is evaporated to remove to obtain a modified chlorinated paraffin; The mass ratio of the chlorinated paraffin to ether is 10:65; The mass ratio of the ether solution of the chlorinated paraffin, 2-thiol methylbenzimidazole, and polyglycerol-10 polyricinoleate is 1000:5:33; The model of the chlorinated paraffin is chlorinated paraffin 70#.

[0016] The preparation method of the PVC-ABS alloy material is: PVC resin, chlorinated polyethylene resin, modified chlorinated paraffin, plasticizer and lubricant of specified mass in the raw materials are mixed in a high-speed mixer at a controlled temperature of 120°C for 20 minutes. After the mixing is completed, ABS resin and glycidyl ester-modified titanium dioxide of specified mass in the raw materials are added to the mixer, the temperature is adjusted to 190°C, and the mixing is carried out for 30 minutes. After the mixing is completed, extrusion granulation is carried out to obtain a PVC-ABS alloy material. Example 2

[0017] A highly impact-resistant flame-retardant PVC-ABS alloy material, wherein the raw materials include PVC resin, ABS resin, chlorinated polyethylene resin, glycidyl ester-modified titanium dioxide, modified chlorinated paraffin, plasticizer, lubricant, and flame retardant, and the mass ratio of the raw material components is 43:6.5:52:1.8:0.9:0.45:0.75:0.45; The model of the PVC resin is S-550; The model of the ABS resin is DA-05-B; The model of the chlorinated polyethylene resin is CPE-132-C; The plasticizer is dioctyl terephthalate; The lubricant is tetrapentyl stearate; The flame retardant is antimony trioxide; The preparation method of the glycidyl ester-modified titanium dioxide comprises acetoacetic acid treatment and glycidyl ester modification; The method of the acetoacetic acid treatment is: The temperature is controlled to be 1350° C., titanium dioxide is placed in a muffle furnace for calcination, the calcination time is 370 minutes, and after the calcination is completed, it is naturally cooled to room temperature, and then mixed with acetoacetic acid solution, the temperature is controlled to be 4° C., the stirring speed is controlled to be 1750 r / min, and rapid stirring is performed for 4 minutes. After the stirring is completed, it is washed and dried to obtain acetoacetic acid treated titanium dioxide; The mass ratio of the titanium dioxide to the acetoacetic acid solution is 6.5:40; The titanium dioxide is rutile titanium dioxide with a particle size of 17 μm; The concentration of the acetoacetic acid solution is 7.0 wt %.

[0018] The glycidyl ester modified method is: The titanium dioxide treated with acetoacetic acid is mixed with tetrahydrofuran and stirred evenly to obtain a titanium dioxide dispersion, and then glycidyl acrylate is added to the titanium dioxide dispersion, the temperature is controlled to be 18°C, and the stirring is performed for 85 minutes. After the stirring is completed, the temperature is adjusted to 52°C, and the stirring is continued for 15.5 hours. After the stirring is completed, the titanium dioxide modified with glycidyl acrylate is obtained by filtering, washing with alcohol, and drying. The mass ratio of the acetoacetic acid treated titanium dioxide, tetrahydrofuran and glycidyl acrylate is 6.5:35:10.

[0019] The preparation method of the modified chlorinated paraffin is: The chlorinated paraffin and ether are mixed and stirred to completely dissolve to obtain a chlorinated paraffin ether solution, and then the stirring speed is controlled to 50 r / min, and 2-thiol methylbenzimidazole and polyglycerol-10 polyricinoleate are added to the chlorinated paraffin ether solution while maintaining continuous stirring. After the addition is completed, the temperature is controlled to 69° C., the stirring speed is controlled to 100 r / min, and stirring is performed for 70 minutes. After the stirring is completed, the solvent ether is evaporated to obtain a modified chlorinated paraffin; The mass ratio of the chlorinated paraffin to ether is 10:60; The mass ratio of the ether solution of the chlorinated paraffin, 2-thiol methylbenzimidazole, and polyglycerol-10 polyricinoleate is 750:4.5:27; The model of the chlorinated paraffin is chlorinated paraffin 70#.

[0020] The preparation method of the PVC-ABS alloy material is: PVC resin, chlorinated polyethylene resin, modified chlorinated paraffin, plasticizer and lubricant of specified mass in the raw materials are mixed in a high-speed mixer at a controlled temperature of 115°C for 25 minutes. After the mixing is completed, ABS resin and glycidyl ester-modified titanium dioxide of specified mass in the raw materials are added to the mixer, the temperature is adjusted to 185°C, and the mixing is carried out for 35 minutes. After the mixing is completed, extrusion granulation is carried out to obtain a PVC-ABS alloy material. Example 3

[0021] A highly impact-resistant flame-retardant PVC-ABS alloy material, wherein the raw materials include PVC resin, ABS resin, chlorinated polyethylene resin, glycidyl ester-modified titanium dioxide, modified chlorinated paraffin, plasticizer, lubricant, and flame retardant, and the mass ratio of the raw material components is 47:7.5:58:2.2:1.1:0.55:0.85:0.55; The model of the PVC resin is S-550; The model of the ABS resin is DA-05-B; The model of the chlorinated polyethylene resin is CPE-132-C; The plasticizer is dioctyl terephthalate; The lubricant is tetrapentyl stearate; The flame retardant is antimony trioxide; The preparation method of the glycidyl ester-modified titanium dioxide comprises acetoacetic acid treatment and glycidyl ester modification; The method of the acetoacetic acid treatment is: The temperature is controlled to be 1450° C., titanium dioxide is placed in a muffle furnace for calcination, the calcination time is 350 minutes, and after the calcination is completed, it is naturally cooled to room temperature, and then mixed with acetoacetic acid solution, the temperature is controlled to be 6° C., the stirring speed is controlled to be 1250 r / min, and rapid stirring is performed for 6 minutes. After the stirring is completed, it is washed and dried to obtain acetoacetic acid treated titanium dioxide; The mass ratio of the titanium dioxide to the acetoacetic acid solution is 7.5:40; The titanium dioxide is rutile titanium dioxide with a particle size of 17 μm; The concentration of the acetoacetic acid solution is 8.0 wt %.

[0022] The glycidyl ester modified method is: The titanium dioxide treated with acetoacetic acid is mixed with tetrahydrofuran and stirred evenly to obtain a titanium dioxide dispersion, and then glycidyl acrylate is added to the titanium dioxide dispersion, the temperature is controlled to 22° C., and the stirring is performed for 75 minutes. After the stirring is completed, the temperature is adjusted to 58° C. and the stirring is continued for 14.5 hours. After the stirring is completed, the titanium dioxide modified with glycidyl acrylate is obtained by filtering, washing with alcohol, and drying. The mass ratio of the acetoacetic acid treated titanium dioxide, tetrahydrofuran and glycidyl acrylate is 7.5:45:14.

[0023] The preparation method of the modified chlorinated paraffin is: The chlorinated paraffin and ether are mixed and stirred to completely dissolve to obtain an ether solution of the chlorinated paraffin, and then the stirring speed is controlled to 70 r / min, and 2-thiol methylbenzimidazole and polyglycerol-10 polyricinoleate are added to the ether solution of the chlorinated paraffin while maintaining continuous stirring. After the addition is completed, the temperature is controlled to 65° C., the stirring speed is controlled to 150 r / min, and stirring is performed for 50 minutes. After the stirring is completed, the solvent ether is evaporated to obtain a modified chlorinated paraffin; The mass ratio of the chlorinated paraffin to ether is 10:70; The mass ratio of the ether solution of the chlorinated paraffin, 2-thiol methylbenzimidazole, and polyglycerol-10 polyricinoleate is 1250:5.5:38; The model of the chlorinated paraffin is chlorinated paraffin 70#.

[0024] The preparation method of the PVC-ABS alloy material is: PVC resin, chlorinated polyethylene resin, modified chlorinated paraffin, plasticizer and lubricant of specified mass in the raw materials are mixed in a high-speed mixer at a controlled temperature of 125°C for 15 minutes. After the mixing is completed, ABS resin and glycidyl ester-modified titanium dioxide of specified mass in the raw materials are added to the mixer, the temperature is adjusted to 195°C, and the mixing is carried out for 25 minutes. After the mixing is completed, extrusion granulation is carried out to obtain a PVC-ABS alloy material.

[0025] Comparative Example 1 Different from Example 1, in the preparation method of glycidyl ester-modified titanium dioxide, the acetoacetic acid treatment step is omitted, and the untreated titanium dioxide is directly glycidyl ester-modified while the amount remains unchanged. The remaining steps are the same to prepare the PVC-ABS alloy material.

[0026] Comparative Example 2 Different from Example 1, in the preparation method of glycidyl ester-modified titanium dioxide, the glycidyl ester modification step is omitted, and the titanium dioxide treated with acetoacetic acid is directly used as the raw material of the PVC-ABS alloy material, and the PVC-ABS alloy material is prepared while the amount remains unchanged.

[0027] Comparative Example 3 The difference from Example 1 is that untreated chlorinated paraffin is used instead of modified chlorinated paraffin as the raw material of PVC-ABS alloy material, and the PVC-ABS alloy material is prepared while the amount remains unchanged.

[0028] Test Example 1 Tensile Properties Test of Alloy Materials The PVC-ABS alloy materials of Examples 1-3 and Comparative Examples 1-3 were used to prepare samples according to the method in GB / T1040.1-2018, and the tensile strength and tensile modulus of the alloy materials were tested. The results are shown in Table 1.

[0029] Table 1

[0030] In Example 1-3, titanium dioxide is treated in two steps, glycidyl ester-modified titanium dioxide is used as an inorganic filler, and chlorinated paraffin is specially treated to finally prepare an alloy material, which has excellent tensile properties, high tensile strength and tensile modulus; Comparative Example 1 In the preparation method of glycidyl ester-modified titanium dioxide, the acetoacetic acid treatment step is omitted, and the titanium dioxide without acetoacetic acid is directly glycidyl ester-modified and used as a raw material, which will cause a serious decrease in the tensile strength and tensile modulus of the alloy material; Comparative Example 2 omitted the glycidyl ester modification step and directly used the titanium dioxide treated with acetoacetic acid as the raw material of the alloy material, which would result in a significant decrease in the tensile strength and tensile modulus of the alloy material. In Comparative Example 3, untreated chlorinated paraffin is used instead of modified chlorinated paraffin as the raw material of the alloy material, which will cause a certain degree of decrease in the tensile strength and tensile modulus of the alloy material.

[0031] Test Example 2: Impact resistance test of alloy materials The PVC-ABS alloy materials of Examples 1-3 and Comparative Examples 1-3 were used to prepare samples according to the method in GB / T1043.1-2008, and the impact strength of the alloy materials was tested, including notched impact strength and unnotched impact strength. The results are shown in Table 2.

[0032] Table 2

[0033] In Example 1-3, titanium dioxide is treated in two steps, glycidyl ester-modified titanium dioxide is used as an inorganic filler, and chlorinated paraffin is specially treated to finally prepare an alloy material. The alloy material has excellent impact resistance, and both notched impact strength and unnotched impact strength are high; Comparative Example 1 In the preparation method of glycidyl ester-modified titanium dioxide, the acetoacetic acid treatment step is omitted, and the titanium dioxide without acetoacetic acid is directly glycidyl ester-modified and used as a raw material, which will cause the notched impact strength and unnotched impact strength of the alloy material to decrease to a large extent; Comparative Example 2 omitted the glycidyl ester modification step and directly used the titanium dioxide treated with acetoacetic acid as the raw material of the alloy material, which would cause a serious decrease in the notched impact strength and the unnotched impact strength of the alloy material; In Comparative Example 3, untreated chlorinated paraffin is used instead of modified chlorinated paraffin as the raw material of the alloy material, which will cause a certain degree of decrease in the notched impact strength and unnotched impact strength of the alloy material.

[0034] Test Example 3: Alloy Material Bending Performance Test The PVC-ABS alloy materials of Examples 1-3 and Comparative Examples 1-3 were used to prepare samples according to the method in GB / T9341-2008, and the bending strength and bending modulus of the alloy materials were tested. The results are shown in Table 3.

[0035] Table 3

[0036] In Example 1-3, titanium dioxide is treated in two steps, glycidyl ester-modified titanium dioxide is used as an inorganic filler, and chlorinated paraffin is specially treated to finally prepare an alloy material, which has excellent tensile properties, high tensile strength and tensile modulus; Comparative Example 1 In the preparation method of glycidyl ester-modified titanium dioxide, the acetoacetic acid treatment step is omitted, and the titanium dioxide without acetoacetic acid is directly glycidyl ester-modified and used as a raw material, which will lead to a decrease in the bending properties of the alloy material, and a certain degree of decrease in the bending strength and bending modulus; Comparative Example 2 omitted the glycidyl ester modification step and directly used the titanium dioxide treated with acetoacetic acid as the raw material of the alloy material, which would lead to a decrease in the bending properties of the alloy material, and a certain degree of decrease in the bending strength and bending modulus; In Comparative Example 3, untreated chlorinated paraffin is used instead of modified chlorinated paraffin as the raw material of the alloy material, which will lead to a decrease in the bending properties of the alloy material, and a serious decrease in the bending strength and bending modulus.

[0037] Test Example 4 Flame retardant properties test of alloy materials The flame retardant grade of the PVC-ABS alloy materials of Examples 1-3 and Comparative Examples 1-3 was tested according to the method in ANSI / UL94-2018. The results are shown in Table 4.

[0038] Table 4

[0039] In Example 1-3, titanium dioxide is treated in two steps, glycidyl ester-modified titanium dioxide is used as an inorganic filler, and chlorinated paraffin is specially treated to finally prepare an alloy material, which has excellent flame retardant properties and a high flame retardant grade; Comparative Example 1 In the preparation method of glycidyl ester-modified titanium dioxide, the acetoacetic acid treatment step is omitted, and the titanium dioxide without acetoacetic acid is directly glycidyl ester-modified and used as a raw material, which will lead to a decrease in the flame retardant properties of the alloy material and a decrease in the flame retardant grade; Comparative Example 2 omitted the glycidyl ester modification step and directly used the titanium dioxide treated with acetoacetic acid as the raw material of the alloy material, resulting in a decrease in the flame retardant properties of the alloy material and a serious decrease in the flame retardant grade; In Comparative Example 3, untreated chlorinated paraffin is used instead of modified chlorinated paraffin as the raw material of the alloy material, which will lead to a decrease in the flame retardant properties of the alloy material and a decrease in the flame retardant grade.

[0040] Test Example 5: Alloy Material Processing Performance Test The equilibrium torque and maximum torque of the PVC-ABS alloy materials of Examples 1-3 and Comparative Examples 1-3 were measured using a torque rheometer. The model of the torque rheometer was RTNI-55 / 03. The temperature of the torque rheometer was set to 190°C, the speed was set to 30 rpm, and the test time was set to 360 s. The results are shown in Table 5.

[0041] Table 5

[0042] In Example 1-3, titanium dioxide is treated in two steps, glycidyl ester-modified titanium dioxide is used as an inorganic filler, and chlorinated paraffin is specially treated to finally prepare an alloy material. The alloy material has excellent processing performance and can maintain a low equilibrium torque and maximum torque during the processing; Comparative Example 1 In the preparation method of glycidyl ester-modified titanium dioxide, the acetoacetic acid treatment step is omitted, and the titanium dioxide without acetoacetic acid is directly glycidyl ester-modified and used as a raw material, which will lead to the deterioration of the processing performance of the alloy material, and the equilibrium torque and the maximum torque will both increase more seriously; Comparative Example 2 omitted the glycidyl ester modification step and directly used the titanium dioxide treated with acetoacetic acid as the raw material of the alloy material, which resulted in poor processing performance of the alloy material, and a significant increase in both the equilibrium torque and the maximum torque. In Comparative Example 3, untreated chlorinated paraffin is used as the raw material of the alloy material instead of modified chlorinated paraffin, which will lead to the deterioration of the processing performance of the alloy material, and the equilibrium torque and the maximum torque will increase to a certain extent.

[0043] Test Example 6: Thermal stability test of alloy materials The PVC-ABS alloy materials of Examples 1-3 and Comparative Examples 1-3 were used to prepare samples according to the method in GB / T1633-2000, and the Vicat softening temperature of the alloy materials was tested; The PVC-ABS alloy materials of Examples 1-3 and Comparative Examples 1-3 were used to prepare samples according to the method in GB / T2917.1-2002, and the static thermal stability of the alloy materials was tested, and the results were expressed as the color change time of Congo red test paper; The PVC-ABS alloy materials of Examples 1-3 and Comparative Examples 1-3 were tested for their initial decomposition temperatures using a thermogravimetric analyzer, the thermogravimetric analyzer model being TG-209 / F1, the test conditions being set to a nitrogen atmosphere, the temperature being raised from room temperature to 750°C at a rate of 20°C / min, and the temperature at which 1% of the mass of the PVC / ABS alloy material is decomposed is recorded as the initial decomposition temperature; The results are shown in Table 6.

[0044] Table 6

[0045] In Example 1-3, titanium dioxide is treated in two steps, glycidyl ester-modified titanium dioxide is used as an inorganic filler, and chlorinated paraffin is specially treated to finally prepare an alloy material. The alloy material has good thermal stability, a high Vicat softening temperature, good static thermal stability, a long color change time, and a high initial decomposition temperature; Comparative Example 1 In the preparation method of glycidyl ester-modified titanium dioxide, the acetoacetic acid treatment step is omitted, and the titanium dioxide without acetoacetic acid is directly glycidyl ester-modified and used as a raw material, which will lead to the deterioration of the thermal stability of the alloy material, wherein the Vicat softening point decreases more seriously, the static thermal stability also decreases seriously, and the initial decomposition temperature decreases seriously; Comparative Example 2 omitted the glycidyl ester modification step and directly used the titanium dioxide treated with acetoacetic acid as the raw material of the alloy material, which would lead to the deterioration of the thermal stability of the alloy material, wherein the Vicat softening point decreased to a certain extent, the static thermal stability decreased to a greater extent, and the initial decomposition temperature decreased to a certain extent; In Comparative Example 3, untreated chlorinated paraffin is used instead of modified chlorinated paraffin as the raw material of the alloy material, which will lead to the deterioration of the thermal stability of the alloy material, wherein the Vicat softening point decreases to a certain extent, the static thermal stability decreases to a certain extent, and the initial decomposition temperature decreases to a certain extent.

Claims

1. A highly impact-resistant flame-retardant PVC-ABS alloy material, characterized in that: The raw materials of the alloy material include PVC resin, ABS resin, chlorinated polyethylene resin, glycidyl ester-modified titanium dioxide, modified chlorinated paraffin, plasticizer, lubricant, and flame retardant, and the mass ratio of each raw material component is 43-47:6.5-7.5:52-58:1.8-2.2:0.9-1.1:0.45-0.55:0.75-0.85:0.45-0.55; The preparation method of the glycidyl ester-modified titanium dioxide comprises acetoacetic acid treatment and glycidyl ester modification; The method for acetoacetic acid treatment is to control the temperature to 1350-1450° C., place the titanium dioxide in a muffle furnace, calcine for 350-370 min, cool naturally to room temperature after calcination, and then mix it with acetoacetic acid solution, control the temperature to 4-6° C., control the stirring speed to 1250-1750 r / min, stir rapidly for 4-6 min, and wash and dry after stirring to obtain acetoacetic acid treated titanium dioxide; The mass ratio of the titanium dioxide to the acetoacetic acid solution is 6.5-7.5:40; The concentration of the acetoacetic acid solution is 7.0-8.0wt%; The glycidyl ester modification method comprises: mixing acetoacetic acid treated titanium dioxide with tetrahydrofuran, stirring evenly to obtain a titanium dioxide dispersion, then adding glycidyl acrylate to the titanium dioxide dispersion, controlling the temperature to 18-22° C., stirring for 75-85 min, adjusting the temperature to 52-58° C. after the stirring is completed, continuing the stirring for 14.5-15.5 h, filtering, washing with alcohol, and drying to obtain glycidyl ester modified titanium dioxide; The mass ratio of the acetoacetic acid treated titanium dioxide, tetrahydrofuran and glycidyl acrylate is 6.5-7.5:35-45:10-14; The preparation method of the modified chlorinated paraffin comprises the following steps: mixing chlorinated paraffin with ether, stirring to completely dissolve the chlorinated paraffin, obtaining an ether solution of the chlorinated paraffin, and then controlling the stirring speed to 50-70 r / min, adding 2-thiol methylbenzimidazole and polyglycerol-10 polyricinoleate to the ether solution of the chlorinated paraffin while continuously stirring; after the addition is completed, controlling the temperature to 65-69° C., controlling the stirring speed to 100-150 r / min, stirring for 50-70 min, and after the stirring is completed, evaporating and removing the solvent ether to obtain the modified chlorinated paraffin; The mass ratio of the chlorinated paraffin to ether is 10:60-70; The mass ratio of the ether solution of the chlorinated paraffin, 2-thiol methylbenzimidazole and polyglycerol-10 polyricinoleate is 750-1250:4.5-5.5:27-38.

2. The high impact resistant flame retardant PVC-ABS alloy material according to claim 1, characterized in that: Among the raw materials of the alloy material, the model of PVC resin is S-550; the model of ABS resin is DA-05-B; the model of chlorinated polyethylene resin is CPE-132-C; the plasticizer is dioctyl terephthalate; the lubricant is tetrapentyl stearate; and the flame retardant is antimony trioxide.

3. The high impact resistant flame retardant PVC-ABS alloy material according to claim 1, characterized in that: In the acetoacetic acid treatment step, the titanium dioxide is rutile titanium dioxide with a particle size of 17 μm.

4. The high impact resistant flame retardant PVC-ABS alloy material according to claim 1, characterized in that: In the step of modifying the chlorinated paraffin, the model of the chlorinated paraffin is chlorinated paraffin 70#.

5. The method for preparing a highly impact-resistant flame-retardant PVC-ABS alloy material according to claim 1, characterized in that: The preparation method of the PVC-ABS alloy material comprises the following steps: mixing PVC resin, chlorinated polyethylene resin, modified chlorinated paraffin, plasticizer and lubricant of specified mass in the raw materials in a high-speed mixer at a temperature of 115-125° C. for 15-25 min; after mixing, adding ABS resin and glycidyl ester-modified titanium dioxide of specified mass in the raw materials into the mixer, adjusting the temperature to 185-195° C. for 25-35 min; and extruding and granulating to obtain the PVC-ABS alloy material.

Citation Information

Patent Citations

  • Injection molding grade flame retardant PVC / ABS alloy material and preparation method thereof

    CN103509289A

  • High-fluidity and flame-retardant PVC / ABS (acrylonitrile butadiene styrene) alloy material and preparation method thereof

    CN105086283A

  • Low-cost, flame-retardant and weather-resistant ABS / CPE / PVC material and preparation method thereof

    CN111363296A

  • PVC resin composition and products made of the same

    US20100292379A1